Potassium silicate as a resistance elicitor in sweet corn yield traits under water stress (2019)
Plant water stress is a major problem in the Cerrado biome of Brazil. Dry periods and random climatic events cause quality and yield losses in sweet corn plants. Compounds, such as silicon (Si), are being studied to reduce the negative impacts of water stress on agricultural crops. Further tests may allow farmers to increase the use of silicon-based compounds. The objective of this study was to evaluate the production parameters of the sweet corn (Zea mays var. saccharata) (Poaceae) Tropical Plus® hybrid with water stress and potassium silicate doses applied with foliar spraying. A randomized block design with four soil water tensions (15, 30, 45 and 60 kPa) and four potassium silicate doses (0, 6, 12 and 24 L ha-1) was used in a greenhouse. The studied factors, alone or in interaction with each other, did not affect most of the sweet corn yield parameters. The hypothesis that these results may have been partially affected by the presence of silicon are discussed. The sweet corn plant yield was affected mainly by the soil water tension of 60 kPa.